2020
DOI: 10.1103/physrevx.10.011029
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Impact of Teaching Experimentation in Physics Labs

Abstract: While there have been many calls to improve the quality of instructional physics labs, there exists little research on the effectiveness of lab instruction. This study provides a direct comparison between labs that have goals to reinforce physics content to those that emphasize experimentation skills. In this controlled study, all students attended the same lecture and discussion sections, had the same homework and exams, but attended labs that had one of two aims: teaching experimentation or reinforcing conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 39 publications
(96 reference statements)
4
44
0
1
Order By: Relevance
“… 11 , 12 Similarly, student experiences in physics laboratories have been shown to result in improved expert-like experimentation practices, attitudes, and beliefs about experimentation but with no significant impact on exam scores in the associated lecture course. 13 15 On the other end of the spectrum, the literature also features many examples of how technology can be used to prime students for learning in the laboratory. For example, virtual laboratory simulations and technique videos utilized in conjunction with hands-on experiments can improve both cognitive and affective learning compared to hands-on experiments alone.…”
mentioning
confidence: 99%
“… 11 , 12 Similarly, student experiences in physics laboratories have been shown to result in improved expert-like experimentation practices, attitudes, and beliefs about experimentation but with no significant impact on exam scores in the associated lecture course. 13 15 On the other end of the spectrum, the literature also features many examples of how technology can be used to prime students for learning in the laboratory. For example, virtual laboratory simulations and technique videos utilized in conjunction with hands-on experiments can improve both cognitive and affective learning compared to hands-on experiments alone.…”
mentioning
confidence: 99%
“…Experimental skills can be roughly classified as skills required to prepare experiments, skills necessary to carry out experiments, or skills relevant to evaluate experimental data [14]. Recent studies have shown that lab courses focused on teaching experimentation do not necessarily convey less content knowledge than those concentrating on content reinforcement [15].…”
Section: Experimental Skillsmentioning
confidence: 99%
“…To our knowledge, there is no research on the opposite: Students enter a physics lab environment where they are highly constrained in their procedures and outcomes but their prior lab experiences are in physics labs designed to engage students in experimentation (i.e., labs such as those described in Refs. [15][16][17][18][19][20][21][22]). Sudden transitions in instructional environments provide a venue for identifying students' shift in frames throughout a single lab period.…”
Section: Introductionmentioning
confidence: 99%